A comprehensive tool for embodied carbon quantification and supporting mitigation strategies in the Building sector - Miguel Martinho; Joana Fernandes; Ricardo Gomes; Paulo Lourador; Paulo Ferrão (Discover Applied Sciences)
Abstract The building sector is a significant contributor to global greenhouse gas (GHG) emissions, with emissions classified into operational and embodied carbon. Embodied carbon refers to the GHG emissions associated with the life-cycle of materials and construction processes of a building, including raw material extraction, manufacturing, construction, and eventual demolition or waste processing. As decarbonization intensifies, reducing operational energy consumption has gained attention, and the embodied carbon footprint of buildings is becoming an increasingly critical factor in overall emissions. Despite this, efficient methods for assessing embodied carbon that integrate data from diverse sources are still lacking. This study provides a new prototype tool that enables stakeholders to quantify embodied carbon in buildings and to assess the effectiveness of mitigation strategies. A comprehensive database was created, incorporating data from various sources on the embodied carbon of construction materials. The prototype tool allows users to compare material choices and evaluate the impact of factors such as building service life and material lifespan on embodied emissions. The prototype tool was applied to the NorteShopping mall in Matosinhos, Portugal, where the embodied carbon of the building’s shell and core was analyzed. The total embodied carbon of the building was calculated at 33,835 tonnes of CO2eq. The analysis revealed how factors like service life, material lifespan, and material selection influence embodied carbon. A mitigation strategy was developed, leading to a 4.2% reduction in projected emissions. If implemented at the design stage, this strategy could have achieved a 14.3% reduction. The prototype tool demonstrates significant potential for supporting efforts to reduce the environmental impact of the building sector, and its full potential is realized when applied early in the design phase, allowing for the development of effective embodied carbon mitigation strategies before construction begins.